Meiofaunal diversity across a sharp gradient of fjord oxygenation: Insights from metabarcoding and morphology approaches in foraminifera - Phoebe O'Brien; Magali Schweizer; Filip Morin; Astrid Hylén; Elizabeth K. Robertson; Per O.J. Hall; Sophie Quinchard; Irina Polovodova Asteman (Marine Pollution Bulletin, 2026)

Hidden aliens: Application of digital PCR to track an exotic foraminifer across the Skagerrak (North Sea) correlates well with traditional morphospecies analysis - Filip Morin; Marina Antonina Zoe Panova; Magali Schweizer; Marlene Wiechmann; Nicole Eliassen; Per Sundberg; Lili Cluzel‐Burgalat; Irina Polovodova Asteman (Environmental Microbiology, 2023)
The problem of invasive species is a well‐studied one, but knowledge of free‐living unicellular eukaryotic invasive species is lacking. A potentially invasive foraminifer (Rhizaria), Nonionella sp. T1, was recently discovered in the Skagerrak and its fjords. Digital polymerase chain reaction (dPCR) was applied to track the spread of this non‐indigenous species using a new dPCR assay (T1‐1). The use of dPCR appears highly complementary to traditional hand picking of foraminiferal shells from the sediment, and is far less time‐consuming. This study indicates that Nonionella sp. T1 has bypassed the outer Skagerrak strait, instead becoming established in Swedish west coast fjords, constituting up to half of the living foraminiferal community in fjord mouth areas. The ecology of Nonionella sp. T1 and its potential invasive impacts are still largely unknown, but it appears to be an opportunist using several energy sources such as nitrate respiration and kleptoplasty along with a possibly more efficient reproductive strategy to gain an advantage over the native foraminiferal species. Future ecological studies of Nonionella sp. T1 could be aided by dPCR and the novel Nonionella sp. T1‐specific T1‐1 assay.